Development of Communicative Skills of Children with Alalia in the Condition of Multisensory Education - Gencho Valchev; Zhana Georgeva (Педагогически форум)
Speech is a main function, which has a defining meaning for the whole psychological development of the child as a personality. It is subordinate to the objective laws of language and runs through certain stages. At the same time without special and purposeful special-pedagogical intervention speech activity of children at preschool age with alalia isn’t realized spontaneously, preverbal forms of communication aren’t formed, either. One of the conditions is multisensory approach, which suggests using the whole structure of polimodal perception of the child – with the participation of the subdominant channels. In the article the main point of sensory integration is considered. The main focus is on the development of aural impressions, visual perception, tactile-kinesthetic emotions and sense perception, their role in the speech development of children with alalia. Multisensory approach contributes to the development and improvement of the communicative abilities of children with alalia.